Prevalence of and factors associated with lumbar spondylolisthesis in patients with rheumatoid arthritis. Issue 3 (3rd May 2016) - Sugimura, Yusuke; Miyakoshi, Naohisa; Miyamoto, Seiya; Kasukawa, Yuji; Hongo, Michio; Shimada, Yoichi
Abstract: Objectives : To investigate the prevalence of and elucidate risk factors for lumbar spondylolisthesis in patients with rheumatoid arthritis (RA). Methods : From 1843 patients registered to the Akita Orthopedic Group on Rheumatoid Arthritis registry, participants comprised 128 patients who had undergone comprehensive radiographic examinations. The presence of lumbar spondylolisthesis (≥5% slip percentage) was assessed from L1 to L5 on lateral plain radiographs. At the time of radiographic evaluation, we also determined the following: RA disease duration; stage and class of Steinbrocker's classification; serum levels of C-reactive protein (CRP) and matrix metalloproteinase-3; disease activity for RA; history of joint surgery; the presence of cervical spinal instability; and details and doses of medications for RA. Results : Forty-seven (36.7%) patients showed lumbar spondylolisthesis (L4, 48%; L3, 29%; L2, 13%; L5, 10%). Among these, Meyerding Grade was I in 89% and II in 11%. Multivariate analysis showed lumbar spondylolisthesis as significantly and independently associated with higher serum CRP level (odds ratio (OR), 1.50; 95% confidence interval (CI), 1.00–2.25; p  = 0.048) and history of joint surgery (OR, 2.87; 95%CI, 1.22–6.72; p  = 0.015). Conclusions : More than one-third of patients with RA in this cohort had lumbar spondylolisthesis, and significant associations with higher serum CRP levels and history of joint surgery were identified.